Sugarcane Cultivar CP 80-1743 Descriptive Fact Sheet: SS-AGR-118/AG133, 7/2018 - Sandhu, H.S.; Singh, M.P.; Gilbert, R.A. (EDIS, 2018)
The selection of a sugarcane cultivar that eventually becomes a production success is probably due in equal parts to the cultivar's attributes, word of mouth, gut feeling, and luck. This fact sheet provides many of the attributes cultivar identification is based upon. Some of these you will use as the basis for cultivar selection. First published Dec. 2001.